APPLICATION DESIGN OF ANDROID-BASED HIJAIYAH LETTERS FOR EARLY AGE CHILDREN AS APPLYING A TEACHING LAMPUNG - Aprianto, Rudi (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2020)
In today's technology development is very rapid. Children are very familiar with electronic media, especially android smartphones, even among young children. There are so many smartphones with features that can take up almost all the children's time every day just to interact with applications on a smartphone. Then the need for applications to help parents educate their children in matters of religion. The purpose of this application is to help young children learn hijaiyah letters and participate in the success of the Lampung Koran program. This application is equipped with image and object features in Arabic and Indonesian. Besides this application is also expected to help parents or teachers deliver material with more interesting methods.